Fanconi Syndrome Induced by Concomitant HIV PrEP and Tacrolimus - Becky S. Linn PharmD; Jeremy W. Vandiver PharmD; Dylan Ren PharmD; Joseph Shassetz PharmD (SAGE Publishing, 2021)
Fanconi syndrome (FS) is a severe grade of drug-induced proximal tubule toxicity. There are numerous causes for acquired FS, and drug toxicity is one of the most common. FS is known to be associated with the nucleoside reverse transcriptase inhibitor (NRTI) tenofovir disoproxil fumarate (TDF). TDF is often used in combination with emtricitabine (FTC) for preexposure prophylaxis (PrEP) of human immunodeficiency virus (HIV) infection. TDF/FTC-induced FS has been observed as a dose-related phenomenon that is directly correlated to kidney function, high levels of absorption of the drug into the proximal tubule, and interactions with other medications. This case report describes a patient who acquired FS after starting TDF/FTC for PrEP in the setting of chronic kidney disease (CKD) with concomitant tacrolimus therapy, a known nephrotoxic agent.